Enhancing Self-Esteem in Classroom Language Learning: The Potential of Implementing a Strength-Based Positive Psychology Intervention at Higher Education - Mehry Haddad Narafshan; Samieh Noori (Universitas Jambi, Magister Program of English Education Department, 2018)
Since positive psychology (PP) is a nascent area of research, there are very few empirical studies assessing the impact of positive psychology interventions. Accordingly, this article reports on a quantitative study concerning the use of a positive psychology intervention to develop learners’ self-esteem in the context of higher education in the English as a foreign language (EFL) sector in Iran. Data was collected during the academic year 2016–2017 from a university in Iran using Cooper Smith (1967, 1981) Self Esteem Inventory Adult Form (CSEI-A) , a self-report questionnaire, as the instrument and administering it before and after a TEFL master course. Thirty six university students participated in a five-month long quasi-experimental study. The current study’s primary aim was to investigate in detail the potential of PP intervention for supporting the self-esteem progress in the context in question. The study showed a statistically significant improvement in the self-esteem of the participants in the experimental group after completing the course suggesting positive paths from positive psychology to understanding the strengths, and managing the weaknesses effectively. The encouraging results from this program suggest new avenues for approaching the change of self-esteem.